The burning - Lasky, Kathryn (New York : Scholastic, 2004)
Soren and his band must fly to the mysterious Northern Kingdoms to find allies against the Pure Ones who are about to launch another deadly attack against the great tree.
Keywords: Owls -- Juvenile fiction; Fantasy; Fantasy fiction